2013
DOI: 10.1038/cddis.2013.122
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor inclusions acquire GRP78/BiP to ameliorate androgen-induced protein misfolding stress in embryonic stem cells

Abstract: Commitment of differentiating embryonic stem cells (ESCs) toward the various lineages is influenced by many factors, including androgens. However, the mechanisms underlying proteotoxic stress conferred by androgen receptor (AR) actions on embryonic cell fate remains unclear. Here we show that mouse ESCs display stress-related cellular phenotypes in response to androgens during early phase of differentiation. Androgen induced a significant increase in the percentage of ESCs and embryoid bodies with the intranuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…The possible reason was that autophagy through the ER stress signaling pathway was indispensable for the survival of osteoblasts regardless of whether under oxidative stress or not. Similar findings have been reported by Yang et al [77]. Our findings suggested that the protective role of autophagy against ROS injury was dependent on the up-regulation of PERK and GRP78, although apoptosis of the cells could also be caused by ROS via non ER-stress-mediated cell death pathways [78][79][80].…”
Section: Discussionsupporting
confidence: 91%
“…The possible reason was that autophagy through the ER stress signaling pathway was indispensable for the survival of osteoblasts regardless of whether under oxidative stress or not. Similar findings have been reported by Yang et al [77]. Our findings suggested that the protective role of autophagy against ROS injury was dependent on the up-regulation of PERK and GRP78, although apoptosis of the cells could also be caused by ROS via non ER-stress-mediated cell death pathways [78][79][80].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests a possible interplay between AR signaling and the UPR pathway. It has been reported that AR signaling activated ER stress/UPR in embryonic stem cells . For example, dihydrotestosterone treatment induced significantly higher CHOP mRNA level in embryonic stem cells stably expressing AR than in parental embryonic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…BiP is involved in the action of ATF6 and plays an important role in initiating adaptive ER stress and inhibiting apoptotic ER stress ( 34 ). Androgen induces BiP to dissociate from ATF6 and act as an androgen receptor-interacting protein, suggesting that BiP is a regulator of androgen receptor protein quality control ( 35 ). Thus, we would expect BiP expression levels to increase with the 50-kDa cleaved form of ATF6.…”
Section: Discussionmentioning
confidence: 99%